Lawsone-loaded Niosome and its antitumor activity in MCF-7 breast Cancer cell line: a Nano-herbal treatment for Cancer - Barani, Mahmood (Daru, 2018)
Phytochemicals like Lawsone have some drawbacks that stem from their poor solubility. Low solubility in aqueous mediums results in low bioavailability, poor permeability and instability of phytochemical compounds in biological environments. The aim of this study was to design nanoniosomes containing Lawsone (Law) using non-ionic surfactants and cholesterol. Niosomes were prepared by thin film hydration method (TFH). Then, they were loaded with Henna extract (HLaw) and standard Lawsone (SLaw), and two resulted formulations were compared. The henna extract was analyzed by mass gas chromatography. Size, zeta potential, polydispersity index (PDI) and morphology of the loaded formulations were evaluated by dynamic light scattering (DLS) and scanning electron spectroscopy (SEM). The incorporation and release rate of Law from niosome bilayers were evaluated by UV-Vis spectroscopy. In vitro experiments were carried out to evaluate antitumor activity in MCF-7 cell line. The results showed distinct spherical shapes and particle sizes were about 250 nm in diameter and have negative zeta potentials. Niosomes were stable at 4 °C for 2 months. Entrapment efficiently of both formulations was about 70% and showed a sustained release profile. In vitro study exhibited that using of niosome to encapsulating Law can significantly increase antitumor activity of formulation in MCF-7 cell line compared to Law solution (free Law). Thus, niosomes are a promising carrier system for delivery of phytochemical compounds that have poor solubility in biological fluids. [Figure: see text]